Peran Penyuluhan Terhadap Peningkatan Kompetensi SDM Tentang Wabah Penyakit Mulut Dan Kuku Di Desa Bendosari, Pujon - Dina Nurun Nisa; Siti Azizah (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
This research aims to determine the role of extension program in increasing human resource competency regarding the FMD in Bendosari Village, as measured by the level of success (knowledge, attitudes, and skills). The variables were used: 1) the role of extension as (a motivator, dynamisator, mediator, and facilitator); 2) the level of success (knowledge, attitudes, and skills). This research method was used descriptive additions used the Likert Summated Rating (LSR) scale with a scale of 1-4, qualitative descriptive analysis, quantitative descriptive analysis, and multiple linear regression analysis taken through interviews using a questionnaire. Data analysis was used IBM SPSS 25 and Microsoft Excel. The motivator variable shows a value with an average score of 3.52, the dynamisator variable shows a value with an average score of 3.44, the mediator variable shows a value with an average score of 3.38, and the facilitator variable shows a value with an average score of 3.67, the success rate variable shows a value with an average score of 3.78, and all of the variable classified as high category in the role level. The results of multiple regression analysis show that the role of extension service significantly affects the level of success in increasing human resource competency. The motivator (X1) and facilitator (X4) variables partially have a significant effect on the level of success. Meanwhile, the dynamicator (X2) and mediator (X3) partially do not significantly affect the success level.